The Problem of 'Edwin Drood': A Study in the Methods of Dickens - Nicoll, W. Robertson, Sir (William Robertson), 1851-1923 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Problem of 'Edwin Drood': A Study in the Methods of Dickens" by W. Robertson Nicoll is a literary analysis written in the early 20th century. This work scrutinizes Charles Dickens's unfinished novel, "The Mystery of Edwin Drood," exploring the mysteries and unresolved plots left by Dickens's untimely death. The book delves into key characters and central questions surrounding the fate of Edwin Drood, the identity of Mr. Datchery, and the implications of Dickens$1 (Bs writing methods. The opening of Nicoll's study sets the stage for a detailed exploration of the issues surrounding Dickens$1 (Bs final narrative. It references previous analyses and theories about the incomplete novel, emphasizing that many mysteries remain unsolved. Nicoll introduces the key mysteries highlighted by Cuming Walters, particularly focusing on whether Edwin Drood was murdered and the significance of other characters like Jasper and Datchery. Additionally, he discusses the textual discrepancies found in the published version of the novel, primarily due to John Forster$1 (Bs edits, suggesting that the original intent of Dickens may not have reached the readers as he envisioned. (This is an automatically generated summary.)s
Release date is 2011-06-03
This ebook was transcribed by Les Bowler
Keywords: Cathedrals in literature; Dickens, Charles, 1812-1870. Mystery of Edwin Drood; Murder in literature